Legal Regulation Concepts of Economic Security in Russia and in the USA: Comparative Analysis - Galina S. Belyaeva; Andrey S. Mamin; Irina Kapustina (Communications of International Proceedings, 2020)
The paper deals with the analysis of issues regarding the legal regulation concepts of economic security in Russia and the USA. It is noted that economic security as an object of scientific knowledge and legal regulation is extremely complex due to the fact that that the situation in this area is constantly changing under the influence of institutional changes, aimed at modernizing socio-economic institutions, as well as public administration activity in the field of the economy, civil society development, the national economy sustainable functioning, overcoming technological and industrial backlogs as well as various external and internal threats to the protection of economic rights, freedoms and legitimate interests of the individual, society and state. The paper presents the results of a comparative analysis of the features of legal regulation and ensuring economic security in Russia and the USA with the prospect of using the positive experience of these countries in solving problematic issues that arise in this area.
Keywords: Legal Regulation; Economy; National Security; Economic Security; Concept; The Russian Federation; The USA.